IT ALL STARTS WITH THE GOAL - Jon Aarum Andersen (Dynamic Relationships Management Journal (DRMJ), 2016)
The purpose of this article is to show that three basic concepts in the fields of organization research, corporate governance, management and leadership research come together theoretically. The concepts of goal, activity and goal-attainment constitute a commonality between them. The theoretical bounds are, however, not evident in all writings. The field of organizational research contains as basic concepts owners and goal, while corporate governance deals with the relationship between owners (shareholders), executives and stakeholders. Additionally, the management discipline pertains to an organization to be managed on behalf of the owners. Numerous leadership theories address the behaviors and activities of managers related to goal-attainment. Highlighting these common grounds could help progress in research in one field to be beneficial in the other research areas. They all come together: the fields of organization, corporate governance, management, and theories of leadership. It all starts with the goal of the owners, and it ends with goal-attainment.